Application of combined EO/PMS/Me2+process in organic matter and true color removal from paint manufacturing industry wastewater - Can-Guven, Emine; Guvenc, Senem Yazici; Ilhan, Fatih; Varank, Gamze (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2022)
Treatment of paint manufacturing industry wastewater by electrooxidation (EO) process in which peroxymonosulfate (PMS) and transition metals are added was investigated. In the EO/PMS process, graphite was the cathode while different anode materials (Ti/IrO2, Ti/RuO2, and Ti/SnO2) were used. The anode with the highest chemical oxygen demand (COD) and true color removal efficiency was selected. To determine the catalyst effect on the process, different transition metals (Fe2+, Cu2+, Zn2+) were added and Fe2+ was chosen as the catalyst which provided higher removal efficiency and lower cost. The central composite design was applied for the optimization of the process variables of the EO/PMS/Fe2+ process. Current density, PMS dose, Fe2+ dose, and reaction time were process variables whereas COD and true color removal efficiency were system responses. Under optimum conditions (200 A/m2 current density, 14 mM PMS dose, 2.5 mM Fe2+ dose, 60 min reaction time), the estimated COD and true color removal efficiency by the model were 74.89% and 99.86%, respectively. The experimentally obtained COD and true color removal efficiencies as a result of validation studies were 74.28% and 99.03%, respectively. Quenching experiments showed that hydroxyl and sulfate radicals were both involved in the process.
Keywords: Advanced oxidation; Central composite design; Industrial wastewater treatment; Peroxymonosulfate; Transition metals; RESPONSE-SURFACE METHODOLOGY; ADVANCED OXIDATION PROCESSES; LANDFILL LEACHATE TREATMENT; ELECTROCHEMICAL OXIDATION; DEGRADATION; ACTIVATION; PERSULFATE; ELECTROOXIDATION; TECHNOLOGIES; Environmental Sciences & Ecology; Public, Environmental & Occupational Health